The effectiveness of differentiated learning method in Arabic vocabulary for students at MTs Muhammadiyah 6 Beton - Prasetya Utama, Panji; Nurhadi, Nurhadi; Qomari, Nur (Abjadia : International Journal of Education, 2025)
AbstractArabic language learning often faces various challenges in school institutions, especially at MTS Muhammadiyah 6 Beton which is not pesantren-based, one of which is the lack of basic understanding of vocabulary. This condition causes students with low understanding to feel left behind compared to students who are already proficient. The purpose of this study is to determine the effectiveness of differentiated learning methods on mastery of Arabic vocabulary so that students' understanding increases. The research method used quantitative with experimental type involving all sevent grade students as the object of research at MTs Muhammadiyah 6 Beton Siman Ponorogo, with a population of 20 students. Data collection techniques were carried out with tests and documentation of learning outcomes, then analyzed with normality tests and t-tests. The results showed that the use of differentiated learning methods can improve the mastery of Arabic vocabulary of 7th grade students at MTs Muhammadiyah 6 Beton Siman Ponorogo, so that students are able to understand the material taught. Based on the results of the One sample t-test test, the sig. (2-tailed) value is 0.000 0.05. Thu it can be concluded that Ho is rejected and H1 is accepted. This shows that the differentiated learning method is effective in improving students' vocabulary mastery so that students' understanding and learning outcomes of Arabic language at MTs Muhammadiyah 6 Beton Siman Ponorogo increase. Keywords:Differentiated Learning, Vocabulary, Learning Outcomes, Arabic Language